Voz de crianças e adolescentes deficientes auditivos e pares ouvintes: influência da percepção auditiva da fala na produção vocal - Delgado-Pinheiro, Eliane Maria Carrit [UNESP]; Bonbonati, Jéssica Caroline; Santos, Flávia Rodrigues Dos [UNESP]; Fabron, Eliana Maria Gradim [UNESP] (FapUNIFESP (SciELO), 2020)
PURPOSE: To compare the acoustic and perceptual-auditory results of the hearing impaired children and adolescents with hearing pairs and to correlate these results with parents' reports regarding speech auditory perception. METHOD: The participants were divided into two groups: Group I, 20 hearing-impaired children and adolescents and Group II, 20 children and adolescents with normal hearing. Acoustic analysis of the vowel /a/ and perceptual-auditory assessment of the vowel /a/ and speech were performed. The speech auditory perception of the GI was assessed using the Infant-Toddler Meaningful Auditory Integration Scale and the Meaningful Auditory Integration Scale with adaptation for adolescent participants. The acoustic and perceptual-auditory voice results of the GI and GII were compared and these results were correlated with the performance in the auditory perception of the GI group. RESULTS: The groups I and II presented similar results, differing statistically in the long-term frequency variation (vF0) and the long-term amplitude variation (vAm) parameters of the vowel /a/ and speech resonance parameter. It was found a negative correlation between auditory perception performance with jitter, vF0 and general degree of vowel /a/. CONCLUSION: The vocal quality in GI was similar to their hearing peers in almost all the vocal parameters that were analyzed. The auditory perception influenced jitter, vF0 and general degree of voice parameters, in which hearing-impaired children and adolescents who presented higher scores for auditory perception were also able to keep a more controlled vocal emission.
Voice of hearing impaired children and adolescents and hearing peers: influence of speech auditory perception on vocal production